Mixed problem for nonlinear Eidelman equation with integral term - Korkuna, O.E. (Carpathian Mathematical Publications, 2012)
The mixed problem for the nonlinear Eidelman type equation containing the integral term is considered in a bounded domain. The existence and uniqueness of solution of this problem in Sobolev’s space are proved. Some estimates of this solution are setted depending on the kernel of the operator.